THE EFFORTS OF THE PRINCIPAL IN DEVELOPING STUDENTS' RELIGIOUS ATTITUDES AT CITRA HIGH SCHOOL, SIDOMULYO VILLAGE MEDANG DERAS DISTRICT BATU BARA REGENCY - Sari Atika Parenduri; M.Ali Permadi Siregar (RADJA PUBLIKA, 2022)
This study uses a qualitative method. The results of the research in this thesis, the efforts of the principal in developing the religious attitude of students at SMA Citra Sidomulyo Village, Medang Deras District have been going well. This is from the programs that have been running. In addition, the teachers at SMA Citra Sidomulyo Village, Medang Deras District are also actively involved in carrying out the programs that have been made. In an effort to develop students' religious attitudes at SMA Citra, Sidomulyo Village, Medang Deras District, Islamic Religious Education teachers often provide indirect directions or advice to develop students' religious attitudes. In developing the religious attitudes of students at SMA Citra Sidomulyo, Medang Deras District, the Principal often encounters obstacles that can hinder the development of students' religious attitudes. These obstacles include the presence of teachers who are less disciplined, online games are rampant, students and peers have different backgrounds. Constraints encountered indirectly can hinder the process of developing students' religious attitudes